Comparative Study on Structural Steel Bondek II Decking for Composite Floor Connections: Design Analysis in Compliance with EN1994-1-1:2004 - Faisal Amsyar, Redzuan; Abdul Razak, Abdul Karim; Norsuzailina, Mohamed Sutan; Norazzlina, M.Sa'don; Siti Farhanah, SM Johan (Springer Singapore (under Springer Nature), 2026)
Due to their improved load-bearing capacity and structural efficiency, composite slabs — which combine concrete and profiled steel sheeting — are widely used in modern industrial buildings. The structural performance, durability, and sustainability of these systems are significantly enhanced through the combination of concrete, which provides compressive strength, and Lysaght Bondek II profiled steel sheeting, which acts as tensile reinforcement. In accordance with EN 1994-1-1:2004, this study re-evaluates the design of composite floor systems utilizing Bondek II profiled steel sheeting. The design provisions for composite steel and concrete structures are specified in Eurocode 4: Part 1-1: General rules and building regulations. The objective of this study is to compare the results of manual calculations performed in Microsoft Excel with those obtained using MegaFloor software for both the construction/formwork stage and the composite slab stage. A case study was carried out using Bondek II, a hot-dipped, zinc-coated high-tensile steel sheeting system, considering different span lengths and loading scenarios. The partial shear connection method, in accordance with EN 1994-1-1:2004, was adopted to assess shear resistance and bending moment capacity. The results demonstrated a high level of agreement between the manual calculations and the software outputs, with only minor variations observed in bending moment and shear force values. However, significant differences were identified in the shear (web crippling) capacity, indicating the need for further validation through experimental investigation. Ultimately, the study confirms that MegaFloor software is a dependable tool for composite floor design, complying with both British Standards and Eurocodes. The use of modern software tools alongside conventional design methods improves the accuracy, efficiency, and sustainability of construction practices.